2016
DOI: 10.4103/1817-1737.165296
|View full text |Cite
|
Sign up to set email alerts
|

Are there radiographic, metabolic, and prognostic differences between cavitary and noncavitary nonsmall cell lung carcinoma? A retrospective fluorodeoxyglucose positron emission tomography/computed tomography study

Abstract: AIMS:The prognosis of nonsmall cell lung cancer with cavitation (NSCLC-c) is not well-known. We compared the positron emission tomography/computed tomography (PET/CT) findings and survival data of patients with NSCLC-c patients with those without cavitation (NSCLC-nc).METHODS:Between 7/2004 and 6/2007, cavitary lung lesions were identified in 46/248 patients undergoing fluorodeoxyglucose (FDG) PET/CT for lung nodule characterization or lung cancer staging. Within the same period, 40 of 202 patients with NSCLC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…23 A cavernous tumor response could be assessed by volume assessment for target lesions or fluorodeoxyglucose metabolism. 24,25 We expect that evaluation criteria for tumor cavities is forthcoming. Although the dose of 250 mg apatinib in a second-line setting adopted in this study is not widely recommended, the safety and efficacy observed were promising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 A cavernous tumor response could be assessed by volume assessment for target lesions or fluorodeoxyglucose metabolism. 24,25 We expect that evaluation criteria for tumor cavities is forthcoming. Although the dose of 250 mg apatinib in a second-line setting adopted in this study is not widely recommended, the safety and efficacy observed were promising.…”
Section: Discussionmentioning
confidence: 99%
“…During anti‐angiogenesis therapy, patients with advanced lung cancer commonly developed cavitation in their lung lesions . A cavernous tumor response could be assessed by volume assessment for target lesions or fluorodeoxyglucose metabolism . We expect that evaluation criteria for tumor cavities is forthcoming.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchial smooth muscles affect airway contraction. Both benign and malignant pulmonary cavities form due to the excretion of necrotic material from necrotic tissues [ 13 15 ]. The bronchial wall of the malignant cavity thickens and becomes stiff due to tumor infiltration.…”
Section: Discussionmentioning
confidence: 99%